Valuing ecotourism in Bukit Merah Orang Utan Island, Malaysia based on visitors’ experience (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Mohd-Asri NF, Kamaluddin SN, Dharmalingam S, Idris WMR, Md-Zain BM. 2021. Valuing ecotourism in Bukit Merah Orang Utan Island, Malaysia based on visitors’ experience. Biodiversitas 22: 1543-1549. Ecotourism has been identified as one of the alternative ways of boosting a region's economic status and highlighting the necessity of a healthier tourism sector. Bukit Merah Orang Utan Island (BMOUI) is the only ex-situ conservation center promoting primate ecotourism on the Malay Peninsula. We conducted a primate ecotourism survey at BMOUI to determine six ecotourism expressive valuations for describing the quality of tourists’ visits to BMOUI and estimating tourist’s willingness to pay (WTP) in relation to the entrance fee. Surveys were completed by 100 randomly selected respondents aged at least 18 years. Likert scale items and Cronbach’s alpha were used in the data analyses. Six ecotourism experiences (hedonic, interaction, novelty, comfort, stimulation, and safety values) were further analyzed using statistical software. The results showed that visitors experienced moderate hedonic experience (44.8%), moderate interactive value (42.35%), moderate novelty value (42.5%), medium comfort value (42.5%), medium stimulation value (42.7%), and low security value (37.15%). In addition, the mean WTP, determined by the bidding process, was about RM54.90 per visitor for each visit. The findings of ecotourism experiences and the estimated price can provide important information to BMOUI administrators. This study will contribute indirectly to upgrading the level of awareness of primate conservation aspects among tourists, entrepreneurs, and locals.
Keywords: Primate ecotourism, orangutan, expressive valuation, willingness to pay, primate conservation